Enhanced anti-inflammatory potential of cinnamate-zinc layered hydroxide in lipopolysaccharide-stimulated RAW 264.7 macrophages - Adewoyin, Malik; Megat Nabil Mohsin, Sumaiyah; Arulselvan, Palanisamy; Hussein, Mohd Zobir; Fakurazi, Sharida (Dove Medical Press, 2015)
Background: Cinnamic acid (CA) is a phytochemical originally derived from Cinnamomum cassia, a plant with numerous pharmacological properties. The intercalation of CA with a nanocarrier, zinc layered hydroxide, produces cinnamate-zinc layered hydroxide (ZCA), which has been previously characterized. Intercalation is expected to improve the solubility and cell specificity of CA. The nanocarrier will also protect CA from degradation and sustain its release. The aim of this study was to assess the effect of intercalation on the anti-inflammatory capacity of CA. Methods: In this study, the anti-inflammatory activity of ZCA was investigated and compared with that of nonintercalated CA. Evaluations were based on the capacity of ZCA and CA to modulate the release of nitric oxide, prostaglandin E2, interleukin (IL)-6, tumor necrosis factor alpha (TNF-α), IL-1β, and IL-10 in lipopolysaccharide-induced RAW 264.7 cells. Additionally, the expression of proinflammatory enzymes, ie, cyclooxygenase-2, inducible nitric oxide synthase, and nuclear factor kappa B (NF-κB), were examined. Results: Although both ZCA and CA downregulated nitric oxide, prostaglandin E2, tumor necrosis factor alpha, IL-1β, and IL-6, ZCA clearly displayed better activity. Similarly, expression of cyclooxygenase-2 and inducible nitric oxide synthase were inhibited in samples treated with ZCA and CA. The two compounds effectively inactivated the transcription factor NF-κB, but the anti-inflammatory cytokine, IL-10, was significantly upregulated by ZCA only. Conclusion: The present findings suggest that ZCA possesses better anti-inflammatory potential than CA, while zinc layered hydroxide had little or no effect, and these results were comparable with the positive control.